1999
DOI: 10.1046/j.1365-2761.1999.00191.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of cecropin peptides on bacteria pathogenic to fish

Abstract: The antibacterial effects of synthetic cecropin B and cecropin P1 were tested against the fish‐pathogenic bacteria Vibrio anguillarum, Vibrio salmonicida, Aeromonas salmonicida, Edwardsiella ictaluri and Yersinia ruckeri. Both cecropins were active against all bacteria tested, but the effect was strongly influenced by the growth media used. In brain heart infusion medium, the minimum inhibitory concentrations of cecropin B ranged from 0.3 to 1.3 μm and from 0.3 to 1.0 μm for cecropin P1, except for E. ictaluri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
14
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 19 publications
0
14
0
Order By: Relevance
“…Salt was removed from the aqueous phase by solid phase extraction. The fractions (maximum 100 ml) were separately loaded on to 35 cc Sep-Pak C 18 Vac cartridges (Water Associates, MA, U.S.A.) equilibrated in acidified water (0·05% TFA). After washing with acidified water, three stepwise elutions were performed with 10, 40 and 80% (v/v) ACN in acidified water, respectively.…”
Section: Extraction and Separation Of Antibacterial Factorsmentioning
confidence: 99%
“…Salt was removed from the aqueous phase by solid phase extraction. The fractions (maximum 100 ml) were separately loaded on to 35 cc Sep-Pak C 18 Vac cartridges (Water Associates, MA, U.S.A.) equilibrated in acidified water (0·05% TFA). After washing with acidified water, three stepwise elutions were performed with 10, 40 and 80% (v/v) ACN in acidified water, respectively.…”
Section: Extraction and Separation Of Antibacterial Factorsmentioning
confidence: 99%
“…Brugia pahangi, a human pathogenic nematoda. However, only one paper has been documented in rela tion to the antimicrobial activities of cecropin peptides on fish pathogens including four bacterial species (Kjuul et al, 1999). Neither the antimicrobial activity of the pep tides on the pathogens of the other aquatic organisms such as bivalves and crustaceans nor the cytotoxic effect has been assessed for therapeutic purpose.…”
mentioning
confidence: 99%
“…These results indicate that cecropin peptides provide antimicro bial activity with a broad spectrum, although the growth inhibitory activity was not found against Edwardsiella tarda, Flavobacterium columnare, Flexibacter maritimus and V. vulnificus biogroup II (Table 1). Kjuul et al (1999) reported that Edwardsiella ictaluri was less sensi tive to cecropin, which could be attributed to the struc ture differences in the bacterial cell wall. Zaldivar (1985) found that the outer membrane of F. columnare was surrounded by galactosamine-rich secretion in TEM preparations treated with ruthenium red.…”
mentioning
confidence: 99%
See 2 more Smart Citations